Ultrastructural features of the osteoclasts from Paget's disease of bone in relation to a viral aetiology. Issue 7 (July 1982) - Harvey, L; Gray, T; Beneton, M N; Douglas, D L; Kanis, J A; Russell, R G
Abstract : The ultrastructure of the osteocytes, osteoblasts, osteoclasts, haemopoietic and other connective tissue cells was examined in 27 biopsies from 22 patients with Paget's disease of bone. Electron microscopy showed characteristic nuclear and cytoplasmic inclusions in the osteoclasts of all of the 25 biopsies exhibiting histological evidence of Paget's disease. Such inclusions were absent from all the other types examined. The intranuclear inclusions consisted of stacked rows or complex whorls of tubular filaments with an individual filament diameter of 12-15 nm, often arranged in a paracrystalline array. The frequency of occurrence of inclusions in the osteoclasts and their individual nuclei measured quantitatively in 18 of the biopsies was related to the histological severity of the disease process. The similarity of the observed inclusions to those of paramyxovirus inclusion bodies (particularly measles) support the hypothesis that Paget's disease is a slow virus infection.